2016
DOI: 10.1590/1676-0611-bn-2015-0078
|View full text |Cite
|
Sign up to set email alerts
|

Isotopic variation among Amazonian floodplain woody plants and implications for food-web research

Abstract: Isotopic variation within food sources adds uncertainty to models intended to reconstruct trophic pathways. Understanding this variation is pivotal for planning sampling protocols for food-web research. This study investigates natural variation in C and N stable isotopes among plant species in two western Amazon flooded forests with contrasting watershed biogeochemistry (white-water vá rzea-forest and black-water igapó -forest 13 C values of leaves and fruits were not statistically different between the two si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 65 publications
1
0
0
Order By: Relevance
“…The δ 13 C values of E. crassipes were similar to those reported in other studies [37][38][40][41][42]. The δ 13 C values of S. yagara were lower than those reported in previous studies [37][38][40][41][42], similar to those reported for higher aquatic plants [43,49]. Eutrophication strongly affects the δ 13 C value of higher aquatic plants.…”
Section: Author Copy • Author Copy • Author Copy • Author Copy • Auth...supporting
confidence: 86%
“…The δ 13 C values of E. crassipes were similar to those reported in other studies [37][38][40][41][42]. The δ 13 C values of S. yagara were lower than those reported in previous studies [37][38][40][41][42], similar to those reported for higher aquatic plants [43,49]. Eutrophication strongly affects the δ 13 C value of higher aquatic plants.…”
Section: Author Copy • Author Copy • Author Copy • Author Copy • Auth...supporting
confidence: 86%